A fit for purpose synthesis of Bruton's tyrosine kinase inhibitor GDC-0852. Issue 44 (29th October 2020) - Lim, Ngiap-Kie; Zhang, Haiming; Sowell, C. Gregory; Gosselin, Francis
Graphical abstract: Abstract: The development of an expedient synthesis to GDC-0852 (1 ), a reversible BTK inhibitor drug candidate, is described. The key starting material tricyclic lactam 5 was prepared by an annulation reaction of unprotected piperidine-2-carbaldehyde HCl salt (20 ) and N -Boc piperidine-2, 4-dione 21 in a safe and scalable manner. A highly selective Pd-catalyzed CN coupling of lactam 5 and linker 2a, followed by Suzuki−Miyaura coupling to fragment 8 subsequently provided a direct and convergent access to the penultimate 17 . A simple NaBH4 aldehyde reduction completed the synthesis to GDC-0852 (1 ) in high yield (54% over 3 steps from 5 ) and purity (99.0 A% HPLC).